Towards a More Efficient Training Process in High-Level Female Volleyball From a Match Analysis Intervention Program Based on the Constraint-Led Approach: The Voice of the Players - Fernández-Echeverría, Carmen; Mesquita, Isabel; González-Silva, Jara; Moreno, M. Perla (Frontiers in Psychology, 2021)
The aim of the research was to know the perception of high-level volleyball players of the changes produced (in relation to the previous season) in the efficiency of the training process, after a match analysis intervention program based on the Constraint-led Approach (CLA). The sample consisted of eleven players from a women's volleyball team. The protocol of the intervention program consisted of providing objective, contextualized and systematic information to the coach (adapted to his needs) that would allow understanding the different real game contexts. We used semi-structured interviews to assess players’ perceptions. The athletes perceived changes in training, both in their preparation and development, specifically in greater involvement and organization in preparing the training; in an increase in the specificity and suitability of training tasks according to individual needs; in the representativeness of the restrictions of the game; in a more tactical approach; in the variability of task and in the accountability to achieve the objective proposed. In addition, in the preparation and development for competition, the players detected more game planning; a deeper analysis of the opponents; an objective selection of the most relevant data, an increase in the depth of match analysis and the inclusion of the weekly meeting with the use of video compared to the previous season. These results expose the benefits of coaches incorporate programmes to obtain objective information about the game in their training process.